From Echo to Expression: Learner Experiences with Shadowing Technique for English Speaking Development in an Indonesian EFL Context - Khoirotun Nissak; Dzulfikri Dzulfikri (Abjadia : International Journal of Education, 2026)
The shadowing technique is becoming increasingly popular as a way to develop speaking abilities in EFL (English as a Foreign Language) contexts. However, a few studies have looked into participants' perspectives on how they feel and react to the technique during the learning process. This study seeks to evaluate a learner's experience using the shadowing technique to improve speaking fluency, as well as any challenges encountered during implementation. Using a qualitative case study methodology, data were gathered through a semi-structured interview with a single participant with C1 English competency and prior shadowing experience. Thematic analysis was used to examine the data. The research identified three major elements about the learner's experience: (1) Shadowing as a natural and enjoyable practice, (2) perceived increase in speaking intonation and fluency, and (3) independence and assimilation of learning practices. In terms of challenges, three themes emerged: (1) assisting in matching the pace and intonation of native speakers, (2) lack of confidence and anxiety in speaking, and (3) limited access to learning resources and feedback. These findings indicate that, while shadowing is a promising strategy for developing speaking abilities, its usefulness is dependent on participants' emotional readiness, the availability of feedback, and the adaptation of materials.